Deterioration of streamflow monitoring in Omo-Gibe Basin in Ethiopia - Haile, Alemseged Tamiru; Asfaw, Wegayehu; Rientjes, T.; Worako, A. W. (Informa UK Limited, 2022)
Poor availability and accuracy of streamflow data constrains research and operational hydrology. We evaluated the status of forty streamflow stations and data quality in the Omo-Gibe basin, Ethiopia. The method included a 3-week field inspection of the stations. Inspection of stations followed common WMO guidelines for appropriate gauging sites. Feedback of observers was collected, and the streamflow data was analyzed. Most of the stations were installed on rivers at headwater catchments. Only 17% of the stations were fully operational whereas the remaining stations require major maintenance. Common problems of the time series data include short observation period, large number of missing records, and inhomogeneity. Nearly all observers expressed dissatisfaction due to lack of supervision, uncertain salary payments and lack of recognition of their contribution. The findings of this study indicate the need to investigate the institutional barriers that affected the homogeneity, completeness, and timeliness of the stream data.